Efficiency Differences of Entrepreneurial Activity and Competition Forms - Lydeka, Zigmas; Kavaliauskas, Justas (Ekonomika, 2003)
Traditionally, economic and business management literature analyses the competition forms or strategies of business enterprises independent of the efficiency of their activities comparing to their competitors. There arc distinguished the well-known competition forms like competition by price and/or by quality but this literature does not make an answer to the question: What kind of differences arc of the less efficient (than average) firms comparing them with the more efficient firms in terms of competition?The article deals with this problem theoretically, using different and integrated levels of analysis, e.g. micro-macro analysis. First of all, the concept of “efficiency” is discussed. Most importantly, the limitations of various “real efficiency” terms (for example, real labor or total factor productivity) are revealed and it is argued in favor of “nominal (not deflated) efficiency” terms, because business activity is profit or money seeking activity which does not always result in more quantities of serviceable products to consumers or society in general.Secondly, the article analyses the main possible causes of business activity differences and state that an efficiency of the firm is mostly conditioned by the degree of innovativeness. Thirdly, the positive relation of efficiency and innovativeness allows us to distinguish these stylized types of entrepreneurial subjects: innovators, which implement innovations and that’s why their efficiency is higher than average; imitators. which mostly only follow the actions of innovators, what could be also a profitable activity, but their activity in general is less efficient than average. Innovators do imitate too but their higher innovativeness is rather their exclusive feature.Ultimately, the authors are trying to answer the question how innovators (or more efficient firms) and imitators (or less efficient firms) compete with each other. Obviously, innovators compete in various branches of economy very differently, c.g. with higher quality and/or lower price, whereas it could be argued that the less efficient firms compete largely with lower prices; also the lower price could be achieved because of the worse quality. It is better for the less efficient entrepreneurs to orient themselves toward the fulfillment of imitations instead of their sudden attempt to become innovators. Most likely it is easier to raise efficiency level by successful imitation and gradual raise of their innovativeness benchmark. Namely this statesman requires a better empirical support.The connection between appropriate entrepreneurial subjects’ efficiency and their used competition forms, might be defined as follows: the less efficient firms compete largely using lower prices, whereas when efficiency rises, the variety of competition forms goes up as well.